Dataset: Forage grasses in crop fields from ultra-high spatial resolution UAV-based imagery - Cardoso Arango, Juan Andres; Jauregui, Rosa Noemi; Camelo-Munevar, Rodrigo Andres; Ruiz-Hurtado, Andres Felipe; Arrechea-Castillo, Darwin Alexis (2025)
This dataset contains orthomosaics and individual Regions of Interest (ROIs) of forage grasses in crop fields from experimental trials of CIAT’s tropical forages breeding program; and annotations in Common Objects in Context (COCO) format derived from that data. The ROIs were manually annotated on UAV imagery and exported in common objects in context (COCO) format compatible with different machine learning models and architectures. 9,554 ROIs in the geospatial data and 12,365 annotations of forage grasses in COCO format.